1964
DOI: 10.1126/science.145.3632.586
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Polysaccharides of Algae: Effects on Life-Support Systems

Abstract: The amount of extracellular polysaccharide produced by eight species of green and blue-green algae ranges from 174 milligrams per liter to 557 milligrams per liter. Most of the polymers are composed of four monosaccharides: a hexose, a pentose, a methyl pentose, and uronic acid. The production of excessive amounts of these photosynthetic end products will undoubtedly influence the effective recycling time of growth media in life-support systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 8 publications
3
42
1
2
Order By: Relevance
“…Moore and Tischer (1964) reported that the EPS of Anabaena flos-aquae and Palmella mucosa were derived from their water-soluble cellular polysaccharides that had the same composition. However, the EPS of N. sphaeroides examined in the present study contained very little carbohydrate and thus could not be considered a polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Moore and Tischer (1964) reported that the EPS of Anabaena flos-aquae and Palmella mucosa were derived from their water-soluble cellular polysaccharides that had the same composition. However, the EPS of N. sphaeroides examined in the present study contained very little carbohydrate and thus could not be considered a polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic plants, such as algae, are able to secrete many organic compounds, such as amino acids and polysaccharides, which are in turn used by bacteria as substrates for growth (14,19,20,23). For example, low-molecular-mass products (Ͻ700 Da) are an important source of carbon for heterotrophic bacteria (19).…”
Section: Discussionmentioning
confidence: 99%
“…This AOM can be considered representative of the various compounds that could be released by any algae because the composition and the metabolism of the algal cells are relatively similar among the various groups of algae, especially in the Chlorophyceae group (5,13). Indeed, because of their metabolism (photosynthesis), algae produce large quantities of organic compounds, such as monosaccharides and polysaccharides, uronic acids, peptides, and amino acids (32,40,41), that are likely to be released during oxidation. The reserve substances are always composed of polysaccharides-glucanes (glucose polymeres) belonging to the family of starches or laminarines.…”
Section: Discussionmentioning
confidence: 99%